Analisis Manajemen Usahatani Kopi di Kecamatan Malangbong Kabupaten Garut, Jawa Barat - Darkiman Ruminta - (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
The contribution of coffee to the national economy is very important, especially as a foreign exchange earner, a source of income for farmers, a producer of industrial raw materials and the provision of employment opportunities (BPS, 2022). People's coffee plantations still have many obstacles, including; still low production, productivity and product quality; coffee farmer institutions are still weak; limited business partnership between farmers and industry (Ditjenbun, 2022). The reality in the field is that many coffee plants are damaged and old and pest/plant disease attacks are increasing. The government has carried out a coffee plant development program through assistance in rejuvenating coffee plants to farmers, one of which is coffee farmers in Malangbong, Garut Regency. The aim of this research is to determine the farming management of coffee farmers in Malangbong, Garut Regency. This research uses qualitative methods and quantitative methods to analyze farming calculations. The results show that the characteristics of coffee farmers in the Regency research location are those of a productive age ranging from 15-64 years (95.18%) with a low level of education (57.32%), but have long experience in cultivating coffee (70.44% ) with own land ownership (81.48%). General results of the implementation of farm management such as management functions; planning, organizing, implementing, monitoring and evaluating have been carried out by coffee farmers. The farming income of coffee farmers is IDR 9,622,782 ha/year and this value is relatively lower when compared to other areas, because most of the coffee plants in Malangbong are old plants and are only rejuvenated at 3-4 years of planting age so the harvest results are not optimal.